Pendidikan karakter; pembentukan cinta tanah air dan kreativitas peserta didik melalui program parktik membatik jumputan di sekolah dasar - Farah Oktaviana; Syarip Hidayat; Ahmad Mulyadiprana (IKIP Siliwangi, 2024)
Abstract The activities of the batik jumputan practice program have an important role, especially in the development of character education which is included in the character of love for the homeland and creativity of students in elementary schools. The holding of batik learning in schools that aims to preserve the local wisdom of batik products in the form of cultural arts learning where students can develop their talent interests can be seen from the knowledge, skills, and attitudes in students. The process of learning activities for batik practice is so that students know and understand how the steps of making batik from beginning to end and can develop creative ideas that arise to determine the desired motives of students. The focus of this research also aims to find out how to plan, implement, apply and evaluate both supporting and inhibiting factors in the development of the character of love for the homeland and creativity of students through the practice of batik jumputan. The subjects in this study were teachers and grade 5 students totaling 20 people. However, there are 4 students who are observed specifically to be described according to the characters developed in the practice of batik jumputan. Data collection is carried out through interviews, observations, questionnaires, and documentation techniques. The approach used from this research is a qualitative approach with a descriptive method which explains what happens in the field. Based on the results of trials or observations made, it shows that the character of love for the homeland and creativity of students are quite developed and understand ideally through the practice program of batik jumputan. The feasibility results of the trial obtained the percentage obtained through the student questionnaire were 89.6% with the criteria of